CHARACTERIZATION OF INULIN FROM BLACK SALSIFY (SCORZONERA HISPANICA L.) FOR FOOD AND PHARMACEUTICAL PURPOSES - Petkova, Nadezhda (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the current study was to evaluate the black salsify (Scorzonera hispanica L.) as a potential source of inulin and to characterize the physicochemical properties of isolated polysaccharide. Methods: The carbohydrate content in its roots and leaves was analyzed by high-performance liquid chromatography with refractive index detection (HPLC-RID) method. Microwave-assisted extraction was performed for isolation of inulin from black salsify roots. The obtained polysaccharide was characterized by HPLC-RID method, HPLC size-exclusion chromatography, and Fourier transformed-infrared spectroscopy. Functional properties as swelling capacity, solubility, and water-holding and oil-holding capacities (OHCs) were also evaluated. Results: Black salsify (S. hispanica L.) roots were evaluated as a rich source of inulin (22% dw) and 1-kestose (6.25 g/100 g dw). The isolated inulin (yield 20%) was characterized with average degree of polymerization 17, with polydispersity index (1.04) that was near to medium-chained inulin. This polysaccharide showed better OHC than water-holding capacity, and it was characterized with swelling capacity 0.5 ml/g sample. Conclusion: For the first time, inulin was isolated from black salsify roots. The chemical characterization of inulin reveals the potential of this plant to be used as a valuable source of this polysaccharide for future application in food technology and pharmaceutical industry for dietary fibers, stabilizer, and coating agent.